1973
DOI: 10.1161/01.res.33.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Control of Canine Abdominal Aorta

Abstract: In anesthetized dogs the peripheral ends of the cut sympathetic chains (LGi-LG 2 level) were stimulated while blood pressure was held constant artificially, and the diameter of the abdominal aorta was monitored. Bilateral stimulation induced a reduction in diameter that was directly related to the stimulation frequency. Maximal diameter reduction of the aorta above the iliac bifurcation averaged 8.01 ± 0.74* of resting diameter. The half-time of contraction (36.5 ±2.1 to 51.5 ± 3 . 6 seconds) was indirectly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…This possibility was examined by measuring the aortic diameter during sympathetic stimulation. Gerova et al (1973) found that, when increases in arterial pressure were prevented, sympathetic stimulation reduced the diameter of the distal abdominal aorta by 8% but did not constrict the proximal abdominal aorta. We found that stellate stimulation did not produce detectable changes in diameter of the thoracic aorta unless arterial pressure changed.…”
Section: Discussionmentioning
confidence: 97%
“…This possibility was examined by measuring the aortic diameter during sympathetic stimulation. Gerova et al (1973) found that, when increases in arterial pressure were prevented, sympathetic stimulation reduced the diameter of the distal abdominal aorta by 8% but did not constrict the proximal abdominal aorta. We found that stellate stimulation did not produce detectable changes in diameter of the thoracic aorta unless arterial pressure changed.…”
Section: Discussionmentioning
confidence: 97%
“…The major fraction of prior work on aortic elastic properties has been performed on excised vessels or vessel strips (Bergel, 1972;McDonald, 1974;Roach and Burton, 1959;Learoyd and Taylor, 1966;Roach, 1970;Berry et al, 1975;Cox et al, 1976;Alexander, 1954;Vatner and Braunwald, 1975), or in anesthetized animals (Bergel, 1972;McDonald, 1974;Pieper and Paul, 1969;Aars, 1971;Nicolosi and Pieper, 1971;Pagani et al, 1975;Patel and Vaishnav, 1972;Gow, 1972;Gow and Taylor, 1968;Cox, 1975;Gow, 1970;Alexander, 1954;Wiggers and Wegria, 1938;Peterson et al, 1960;Patel et al, 1961;Remington, 1962;Gerova et al, 1973). In 1972, Gow noted that "new techniques are required to produce a continuous monitor of vascular dimensions in conscious animals, thus allowing the precise measurement of the normal physiological variations in vascular calibre and viscoelastic properties."…”
Section: Discussionmentioning
confidence: 99%
“…Its spring resistance has 10~2 N at an opening of 0.46 cm. Since this load was distributed over the length of the feet (0.5 cm), the interference to normal diameter pulsation would be negligible (Gerova et al, 1973). The frequency response of the caliper was tested by holding one leg and attaching the other to a mechanical oscillator driven by a servomotor.…”
Section: Coronary Artery Measurements On the Beating Heartmentioning
confidence: 99%